2017
DOI: 10.1017/9781139028271
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Suitability and Distribution Models

Abstract: This book introduces the key stages of niche-based habitat suitability model building, evaluation and prediction required for understanding and predicting future patterns of species and biodiversity. Beginning with the main theory behind ecological niches and species distributions, the book proceeds through all major steps of model building, from conceptualization and model training to model evaluation and spatio-temporal predictions. Extensive examples using R support graduate students and researchers in quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
1,250
0
26

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,064 publications
(1,282 citation statements)
references
References 0 publications
6
1,250
0
26
Order By: Relevance
“…A total of 10,000 global pseudoabsence records were randomly generated, and a five-fold crossvalidation approach with 10 repetitions was adopted to evaluate predictive performance of 10 algorithms. Relative contribution of each predictor variable and response curves of important variables were determined (Guisan et al, 2017;Thuiller et al, 2014). Algorithms with TSS over 0.85 and AUC over 0.90 for both species were selected to develop committee averaging ensemble models (Costa, Muelbert, Vieira, & Castello, 2015;Thuiller et al, 2014).…”
Section: Modelling Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 10,000 global pseudoabsence records were randomly generated, and a five-fold crossvalidation approach with 10 repetitions was adopted to evaluate predictive performance of 10 algorithms. Relative contribution of each predictor variable and response curves of important variables were determined (Guisan et al, 2017;Thuiller et al, 2014). Algorithms with TSS over 0.85 and AUC over 0.90 for both species were selected to develop committee averaging ensemble models (Costa, Muelbert, Vieira, & Castello, 2015;Thuiller et al, 2014).…”
Section: Modelling Proceduresmentioning
confidence: 99%
“…There are a number of modelling approaches available for SDM studies including classification, regression, and machine learning methods. To reduce the model-based uncertainty and produce reliable predictions, the ensemble modelling technique has been proposed and frequently used, which combines prediction results of multiple modelling algorithms thus can reduce the uncertainties in model predictions (Araújo & New, 2007;Guisan et al, 2017;Thuiller et al, 2014Thuiller et al, , 2019. Previous studies have revealed that different single modelling algorithms have different predictive ability and can produce largely variable results (Elith & Graham, 2009;Pearson et al 2006;Qiao et al, 2015).…”
Section: Potential Distributions Under Current and Future Climate Smentioning
confidence: 99%
See 1 more Smart Citation
“…These methods have been used since the 1920s (Cook, 1925;Sutherst, 2014), but recent years have seen rapid growth in the number of studies employing SDM in fields including ecology, conservation biology, evolutionary biology and epidemiology (Allen & Lendemer, 2016;Coro, Pagano, & Ellenbroek, 2013;Guisan, Thuiller, & Zimmermann, 2017;Gutierrez-Tapia & Palma, 2016;Lezama-Ochoa et al, 2016;Peterson et al, 2011;Raghavan et al, 2016). These methods have been used since the 1920s (Cook, 1925;Sutherst, 2014), but recent years have seen rapid growth in the number of studies employing SDM in fields including ecology, conservation biology, evolutionary biology and epidemiology (Allen & Lendemer, 2016;Coro, Pagano, & Ellenbroek, 2013;Guisan, Thuiller, & Zimmermann, 2017;Gutierrez-Tapia & Palma, 2016;Lezama-Ochoa et al, 2016;Peterson et al, 2011;Raghavan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Habitat suitability models (HSMs), also known as species distribution models (SDMs) or ecological niche models, are used to model the relationship between geographical occurrences of species and environmental variables (Guisan et al 2013(Guisan et al , 2017. While modelling habitat suitability and species distribution, ecologists must deal with the problem of spatial resolutions, related to species occurrence data (entering the models as a dependent variable) and to environmental data used as predictors (McPherson et al 2006, Guisan et al 2007, Gottschalk et al 2011, Rocchini et al 2011, Moudrý and Šímová 2012, Pradervand et al 2013, Lecours et al 2015.…”
Section: Introductionmentioning
confidence: 99%